Efektivitas ekstrak metanol akar pandan wangi (Pandanus amaryllifolius Roxb.) Sebagai antimalaria terhadap jumlah limfosit dalam darah mencit (Mus musculus) yang diinfeksi Plasmodium berghei - Danang Mustofa; Muhammad Ibnu Kahtan; Diana Natalia; Mistika Zakiah; Ari Widiyantoro (Intisari Sains Medis, 2019)
Malaria is a infectious disease cause by protozoa with genus Plasmodium that is transmitted by female Anopheles mosquito. Our immune system which is role by lymphocyte works specifically when body infected by Plasmodium. The secondary metabolites of Pandan Wangi roots (Pandanus amaryllifolius Roxb.) Â possess as antimalaria. The purpose of this research to know the activity of methanol exctract from roots of Pandan Wangi (Pandanus amaryllifolius Roxb.) as antimalaria on white male mice (Mus muscullus) lymphocyte count infected by Plasmodium berghei. This is a true experimental in vivo with completely randomized design. Antimalaria effect test used methanol extract from roots of Pandan Wangi with concentration 6.5%, 13% and 26%. Positive control group was given 3.74 mg/mL DHP (Dihydroartremisinin-Piperaquin), normal control group was not given any intervention, negative control group was given aquadest. Results of this research show extract with concentration 6.5%, 13% and 26% have the antimalaria effect show by the decrease of parasitemia percentage. In addition, concentration of 26% extract can increase the number of lymphocytes significantly. Extract of Pandan Wangi Roots have antimalaria effect and can increase the number of lymphocytes with the best concentration of 26%. The decreasing number of parasitemia level is not directly related to the increasing of lymphocyte